Keepers of the covenant : frontier missions and the decline of Congregationalism, 1774-1818 - Rohrer, James R. (James Russell), 1960- (Religion in America series (Oxford University Press), 1995)
The first book-length treatment of its topic, this study is aimed at abolishing the old cliche that Congregationalism failed to adapt to the democratizing culture of the westward migration. Drawing on hundreds of previously unused letters, journals, and sermons, the author argues that Congregational missionaries were aggressive evangelists who successfully adjusted to the egalitarian demands of the early republican frontier. Keepers of the Covenant critically examines the various explanations for the decline of Congregationalism after the American Revolution, and in the process, overturns gene.